2020
DOI: 10.1093/jac/dkaa165
|View full text |Cite
|
Sign up to set email alerts
|

Trends, seasonality and the association between outpatient antibiotic use and antimicrobial resistance among urinary bacteria in the Netherlands

Abstract: Objectives To determine trends, seasonality and the association between community antibiotic use and antimicrobial resistance (AMR) in Escherichia coli and Klebsiella pneumoniae in urinary tract infections. Methods We analysed Dutch national databases from January 2008 to December 2016 regarding antibiotic use and AMR for nitrofurantoin, trimethoprim, fosfomycin and ciprofloxacin. Antibiotic use was expressed as DDD/1000 inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 34 publications
7
20
0
Order By: Relevance
“…However, resistance to nitrofurantoin in all 3 species peaked in the winter/spring and lagged use by about 3 to 5.5 months. This was consistent with a previous finding that nitrofurantoin resistance lagged use by 3-6 months in E. coli and K. pneumoniae urinary tract isolates [11]. Quinolones, which are used to treat both respiratory infections and UTIs [27], showed both winter and summer peaks in use, but only a single winter/spring peak in ciprofloxacin resistance in all 3 species.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, resistance to nitrofurantoin in all 3 species peaked in the winter/spring and lagged use by about 3 to 5.5 months. This was consistent with a previous finding that nitrofurantoin resistance lagged use by 3-6 months in E. coli and K. pneumoniae urinary tract isolates [11]. Quinolones, which are used to treat both respiratory infections and UTIs [27], showed both winter and summer peaks in use, but only a single winter/spring peak in ciprofloxacin resistance in all 3 species.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, a study from the Netherlands that analyzed antibiotics with summer/autumn peaks in use (e.g. Nitrofurantoin, Fosfomycin, Trimethoprim) found that resistance in E. coli and Klebsiella pneumoniae still peaked in the winter/spring and lagged use by 3-6 months [11], inconsistent with the Blanquart et al model. The authors of this study attribute the longer lag time to the weaker seasonal fluctuations and lower overall rates of antibiotic use in their study population.…”
Section: Introductionmentioning
confidence: 80%
“…This trend that has been reported before for this organism ( 1 , 8 ), although this is the first time it has been found in the NH setting. Additionally, it is important to caution that although an association between resistance rates and antimicrobial use has been reported in some common gram-negative pathogens in various healthcare settings ( 15 , 16 ), such association may present with a lag, especially when infections are used as the endpoint rather than colonization, presumably at least in part due to the time elapsed between colonization, infection, and eventually collection of clinical samples ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, its importance is often underestimated in community infections, as hospitalized infections gain the most attention [2]. Many previous studies have addressed the prevalence of AR in clinical environments [3][4][5], and more recently AR prevalence in non-hospitalized populations too [6,7]. Most of these studies were conducted on cultivable clinical strains using microbiological methods that involve cultivation and antibiogram tests.…”
Section: Introductionmentioning
confidence: 99%